Text for you : a novel - Cramer, Sofie, 1974- (Penguin Books, 2021)
"Soon to be a major motion picture starring Sam Heughan and Priyanka Chopra Jonas, a heartwarming story of love, loss, serendipity, and texting. After a heated argument, Clara's fiance stormed out of their apartment, but before they have a chance to reconcile, he died a tragic accident. It's been two years, but she's still paralyzed with grief, and her friends are worried about her. So, to try to say what was left unsaid, she start's texting his old phone. What she doesn't realize is that the number has been reassigned. Across town, Sven's phone begins receiving mysterious but heartfelt text messages. He doesn't respond, but is captivated by the sender. His own relationship has been on the rocks, and when it ends he sets out to find the person who has been texting him. Neither Sven nor Clara knew what they were setting out to find, but it would change both of their lives forever"--